2019
DOI: 10.1590/fst.07818
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds, total antioxidant capacity and volatile components of Cabernet Sauvignon red wines from five different wine-producing regions in China

Abstract: The purpose of this study was to elucidate the influence of terroir on the polyphenolic compounds, total antioxidant and aroma components of Cabernet Sauvignon red wines from five different wine-producing regions in China. The results obtained showed that the phenols concentrations and total antioxidant capacities from new wine 1 (NW1) were significantly the highest among five regional wines, the latter were new wine 3 (NW3), old wine 1 (DW1) and new wine 2 (NW2), these parameters in old wine 2 (DW2) were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Ranaweera et al (2021) classified Australian Cabernet Sauvignon wines from three wine regions based on spectrofluorometric and multi-element analyses. Others authors evaluated Cabernet Sauvignon wines from China, and found that PCs profiles and concentrations were dependent of the vineyards locations (Li et al, 2011;Jin et al, 2017;Jiang and Sun, 2019). Another study carried out on 5 different varieties, including Cabernet Sauvignon and cultured with the same environmental conditions, demonstrated the effect of the genotype in the grape phenotype (Aleixandre et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ranaweera et al (2021) classified Australian Cabernet Sauvignon wines from three wine regions based on spectrofluorometric and multi-element analyses. Others authors evaluated Cabernet Sauvignon wines from China, and found that PCs profiles and concentrations were dependent of the vineyards locations (Li et al, 2011;Jin et al, 2017;Jiang and Sun, 2019). Another study carried out on 5 different varieties, including Cabernet Sauvignon and cultured with the same environmental conditions, demonstrated the effect of the genotype in the grape phenotype (Aleixandre et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Phenylpropanol exhibited a distinctive floral scent and was the main aroma compound in Cabernet Sauvignon wine. Group R2 exhibited the highest phenylethanol content, resulting in the most intense floral odor [ 44 ]. The isoamyl alcohol compound was found to possess a cheese-like aroma, and was identified as a possible odorant that might have played a role in the study [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…For a long time, resveratrol was supposed to be a polyphenol responsible for the beneficial effect of red wine, but recently, this opinion is questioned [85]. However, it must be mentioned here, that the effect of wine may be associated with the fact that phenolic compounds, as well as resultant total antioxidant capacity, but also volatile components of red wines may result from the region and its characteristics, including soil type, terrain characteristics, and climate conditions [86].…”
Section: Discussionmentioning
confidence: 95%